Celebrating Shirley Griffenhagen's 59th Birthday - Watkins, Howard::::::::: (1988)
Seated: Shirley Griffenhagen, Robin Watkins, Leslie Prusia, and Adam Watkins: Standing: Jean Anderson (Leslie's mother), Christine Watkins, Maril Turpin, and Frances Kamp